2018
DOI: 10.4038/cbj.v9i2.35
|View full text |Cite
|
Sign up to set email alerts
|

Successful Implementation of the Balanced Scorecard in a Telecommunications Firm: An Institutional Theory Analysis

Abstract: This paper explores how a balanced scorecard (BSC) has been successfully implemented and institutionalised in a leading telecommunications company in Sri Lanka (Telinotec) through improvements over two phases (pre 2012 and post 2012). It adopts a qualitative methodology and case study approach and is founded upon the theoretical underpinnings of institutional theory, more specifically the institutionalisation model of Tolbert and Zucker (1996). The findings suggest that while the BSC was implemented in 2000, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In most studies of BSC practice, the results have mostly concentrated on three perspectives outcomes: financial, internal process, and customer perspectives (Chih-Chao Chung, 2016;Assiri, Zairi, & Eid, 2006;Davis, 2003;Keller, 2011;Lueg, 2015;Malm , 2001;S ra t, 2018;Soderberg, 2017;Thananchayana, 2018). The most important finding of this study is learning and growth perspective is a key factor to HR development and employee wellbeing.…”
Section: Discussion and Implications For Human Research Managementmentioning
confidence: 72%
“…In most studies of BSC practice, the results have mostly concentrated on three perspectives outcomes: financial, internal process, and customer perspectives (Chih-Chao Chung, 2016;Assiri, Zairi, & Eid, 2006;Davis, 2003;Keller, 2011;Lueg, 2015;Malm , 2001;S ra t, 2018;Soderberg, 2017;Thananchayana, 2018). The most important finding of this study is learning and growth perspective is a key factor to HR development and employee wellbeing.…”
Section: Discussion and Implications For Human Research Managementmentioning
confidence: 72%
“…The BSC, developed by Kaplan and Norton, is among the most widely known of the integrated performance measurement systems. Since it was first introduced by Robert Kaplan and David Norton, the BSC has attracted widespread interest from academics and businesses across different industries, from manufacturing to services and from the public to the private sector (Thananchayana, 2018).…”
Section: Balanced Scorecardmentioning
confidence: 99%
“…They indicated an indirect relationship between the BSC's management control function and the improved performance on BSC measures, stating that the managers in their study perceived that improved performance on the BSC would lead to improved efficiency and profitability. • Literature about criticism: • (Thananchayana & Gooneratne, 2018) individual and organizational performance.…”
Section: Balanced Scorecardmentioning
confidence: 99%
“…They indicated an indirect relationship between the BSC's management control performance on BSC measures, stating that the managers in their study perceived that improved performance on the BSC would lead to improved efficiency and profitability. ; (Kasurinen, 2002); (Norreklit, 2000) (Thananchayana & Gooneratne, 2018)Study result noted that the BSC is a key tool to measure departmental, tional performance. While Malina and Selto (2001) suggested that the BSC is an effective tool for communicating strategy, the survey study by Hoque and James (2000) revealed that organizational performance improves with the use of the BSC.…”
Section: The International Journal Of Business and Managementmentioning
confidence: 99%